2006
DOI: 10.1080/03602530600569851
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital Confers its Diverse Effects by Activating the Orphan Nuclear Receptor Car

Abstract: In the early 1960s, phenobarbital (PB) was shown to induce hepatic drug metabolism and the induction was implicated in the molecular mechanism of drug tolerance development. Since then, it has become evident that PB not only induces drug metabolism, but also triggers pleiotropic effects on liver function, such as cell growth and communication, proliferation of the endoplasmic reticulum, tumor promotion, glucose metabolism, steroid/ thyroid hormone metabolism, and bile acid synthesis. Upon activation by PB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 62 publications
(43 reference statements)
0
46
0
Order By: Relevance
“…For example, although peroxisome proliferators have carcinogenic consequences in the livers of rodents, epidemiological studies have revealed that similar effects are unlikely to occur in humans (25). Additionally, PB has been used for decades as the prototypical nongenotoxic tumor-promoting agent in numerous rodent studies of hepatocarcinogenesis; however, epidemiological studies indicate that PB does not cause liver tumors in humans (26). Although the primary event governing activation of nuclear receptors is ligand binding, increasing amounts of evidence suggest that cell signaling pathways and modulation of nuclear receptor-cofactor-phosphorylation status also determines overall responsiveness to environmental stimuli (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although peroxisome proliferators have carcinogenic consequences in the livers of rodents, epidemiological studies have revealed that similar effects are unlikely to occur in humans (25). Additionally, PB has been used for decades as the prototypical nongenotoxic tumor-promoting agent in numerous rodent studies of hepatocarcinogenesis; however, epidemiological studies indicate that PB does not cause liver tumors in humans (26). Although the primary event governing activation of nuclear receptors is ligand binding, increasing amounts of evidence suggest that cell signaling pathways and modulation of nuclear receptor-cofactor-phosphorylation status also determines overall responsiveness to environmental stimuli (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CAR activation may also occur without direct binding of the ligand to CAR, and this is exemplified by the activation of CAR by phenobarbital and various other compounds (12). The reader is referred to recent reviews on the mechanistic details of direct and indirect activation of CAR (17,80) and the interplay between CAR and other nuclear receptors (19).…”
Section: Constitutive Androstane Receptormentioning
confidence: 99%
“…For example, the activation of nuclear receptor CAR by chemicals such as phenobarbital, an anticonvulsant drug, induces various enzymes and transporters, thereby increasing the hepatic activities of drug metabolism and transport (Kodama and Negishi, 2006). CAR target genes include phase I enzymes (e.g., Cyp2b, Cyp2c, and Cyp3a), phase II enzymes (e.g., Sults, Ugts, and Gsts) (Ueda et al, 2002), and transporters such as Mrp2 and Mrp4 (Kast et al, 2002;Assem et al, 2004).…”
Section: Downloaded Frommentioning
confidence: 99%